2020
DOI: 10.18332/ejm/127769
|View full text |Cite
|
Sign up to set email alerts
|

Causal links to missed Australian midwifery care: What is the evidence?

Abstract: INTRODUCTION The incidences and types of missed nursing care in the acute care and community sectors are both ubiquitous and quantifiable, however, there are few research studies relating to the type and frequency of missed maternity-based care for mothers and families. The aim of this study is to estimate the incidences and types of Australian missed midwifery care and to identify those factors that have causal links to it. METHODS A non-experimental, descriptive metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Nurses working in obstetrics and gynaecology often missed maternal care, perhaps because they turned their attention to the newborn and ignored the mother (Haftu et al, 2019). The least commonly missed task was giving reassurances to the family, consistent with the study by Blackman, which may be because nurses helped families gain confidence in caring for their babies through emotional support (Blackman, Hadjigeorgiou, & McNeill, 2020). Nurses in departments other than obstetrics and gynaecology missed ambulation three times per day or as ordered frequently, in agreement with previous studies (Bacaksiz et al, 2020;Willis et al, 2015), which may be because assisting patient ambulation was time-consuming and difficult to do independently.…”
Section: The Impact Of Communication On Missed Nursing Carementioning
confidence: 80%
“…Nurses working in obstetrics and gynaecology often missed maternal care, perhaps because they turned their attention to the newborn and ignored the mother (Haftu et al, 2019). The least commonly missed task was giving reassurances to the family, consistent with the study by Blackman, which may be because nurses helped families gain confidence in caring for their babies through emotional support (Blackman, Hadjigeorgiou, & McNeill, 2020). Nurses in departments other than obstetrics and gynaecology missed ambulation three times per day or as ordered frequently, in agreement with previous studies (Bacaksiz et al, 2020;Willis et al, 2015), which may be because assisting patient ambulation was time-consuming and difficult to do independently.…”
Section: The Impact Of Communication On Missed Nursing Carementioning
confidence: 80%
“…The World Health Organization is largely credited with the introduction of the ‘Five Moments for Hand Hygiene’ framework (Sax et al, 2007), but this study has shown that performing hand hygiene before touching a patient was missed most of all of the five moments, especially by Australian nurses although it was rarely overlooked by Lithuanian and Slovakian nurses. In another recent study, hand washing was the most missed aspect of all midwifery care as reported by Australian midwives (Blackman et al, 2020). Practising hand hygiene, which includes the use of alcohol‐based hand rub and hand washing, is one example of a simple yet effective measure to prevent the spread of highly resistant bacteria and infections in healthcare settings.…”
Section: Discussionmentioning
confidence: 95%
“…These are consistent with the few prior studies reporting domains of perinatal care activities in maternity settings. 33,34,39,51 Treatment, procedures, and medication management are less likely to be reported as missing; on the contrary, documentation, assessments, monitoring, and emotional support during labor are commonly missed. In this study, shortages of labor and material resources were reported as the most significant reasons for why the nursing care is delayed, unfinished, or missed in maternity settings.…”
Section: Discussionmentioning
confidence: 99%